2005
DOI: 10.1093/protein/gzi069
|View full text |Cite
|
Sign up to set email alerts
|

Creation of GPCR-based chemical sensors by directed evolution in yeast

Abstract: G protein-coupled receptors (GPCRs) form a class of biological chemical sensors with an enormous diversity in ligand binding and sensitivity. To explore structural aspects of ligand recognition, we subjected the human UDP-glucose receptor (P2Y14) functionally expressed in the yeast Saccharomyces to directed evolution. We sought to generate new receptor subtypes with ligand-binding properties that would be useful in the development of practical biosensors. Mutagenesis of the entire UDP-glucose receptor gene yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The idea that relative receptor activation by ligands is influenced by both the levels of signaling proteins and the particular G protein signaling system studied is supported by previous studies of a variety of G protein-coupled receptors (Cordeaux et al, 2004;Kenakin, 2007;Urban et al, 2007). The work of Ault and Broach using directed evolution in yeast first suggested an interaction of UDP with the hP2Y 14 -R, and their studies with various mutants of the human P2Y 14 -R also suggested a range of activities of this diphosphate relative to activities observed with UDP-glucose (Ault and Broach, 2006).…”
Section: Discussionmentioning
confidence: 63%
“…The idea that relative receptor activation by ligands is influenced by both the levels of signaling proteins and the particular G protein signaling system studied is supported by previous studies of a variety of G protein-coupled receptors (Cordeaux et al, 2004;Kenakin, 2007;Urban et al, 2007). The work of Ault and Broach using directed evolution in yeast first suggested an interaction of UDP with the hP2Y 14 -R, and their studies with various mutants of the human P2Y 14 -R also suggested a range of activities of this diphosphate relative to activities observed with UDP-glucose (Ault and Broach, 2006).…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, the activity of UDP at the P2Y 14 -R is species-dependent because we observed that UDP is a potent, and apparently full, agonist at the rat P2Y 14 -R. Chambers et al (2000) reported in their initial study of the hP2Y 14 -R that UDP has no agonist activity, and we observed similar results in the studies reported here. Using a reporter system in yeast, Ault and Broach (2006) generated a mutant hP2Y 14 -R displaying a mutation in intracellular loop 1 and various mutations in several of the transmembrane regions. This mutant, selected for its ability to support growth of yeast at lower concentrations of UDP-Glc than the wild-type receptor, exhibited an enhanced UDP-Glc-stimulated response that was inhibited by UDP, and a K B in the micromolar range was reported.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified and developed novel, selective ligands for several P2Y recep-tors that have proven useful for pharmacological resolution of molecularly defined P2Y-R in cells and tissues (Boyer et al, 1996;Houston et al, 2006Houston et al, , 2008Jacobson et al, 2006). Accordingly, we are interested in identifying a selective antagonist for the P2Y 14 -R. Ault and Broach (2006) recently used a yeast model system in which various nucleotides and nucleotide sugars were examined for their ability to stimulate growth of mutant P2Y 14 -R-expressing yeast cells in studies focused on the identification of mutant P2Y 14 receptors with differential agonist sensitivities. Studies performed using one of these mutant receptors revealed that UDP antagonized UDP-Glc-promoted receptor activation in a concentration-dependent manner (Ault and Broach, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of this residue leads to the observed constitutive activity. Thus, more generally, the present methodology has the ability to rapidly isolate mutations that may trap receptors in the active or inactive state, an approach that is complementary to previous work in engineering GPCR selectivity and activity (22,23).…”
Section: Tracing the Effects Of Single Substitutionsmentioning
confidence: 99%